Sectarianism In Aceh: Religious Authorities And The Aswaja Contest - Ramli; Romario (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University (UIN) Jakarta, 2026)
This article investigates the sectarian tensions between the MPU (Ulama Consultative Assembly), the official forum of ulama in Aceh, and the MPTT (Tawhid Tasawuf Study Council), a Sufi community and tariqa (Islamic order). The study adopts a descriptive qualitative methodology, drawing upon news reports, publications, and relevant data pertaining to the conflict between the MPU and the MPTT prior to analysis. The research focuses on Abu Amran Waly, the MPTT, and the responses of the MPU of Aceh — notably several fatwas — concerning his Sufi teachings. The findings indicate that the conflict between the MPU and the MPTT is rooted in theological disputes and a contestation of religious authority. The MPU regards the MPTT as propagating erroneous doctrines, particularly as the influence of the MPTT extends to Java, Kalimantan, and Sulawesi, and even further to Malaysia, Singapore, and Thailand. It is evident that the theological and political-economic dimensions of the conflict are inextricably intertwined.